CHANGES IN STUDENT LEARNING BEHAVIOR IN THE COVID-19 PANDEMIC ERA SMA KRISTEN KAPAN - Wering Martha Kamau; Absalom Oematan (SocioEdu: Sociological Education, 2023)
This qualitative research aims to determine changes in student learning behaviour during the COVID-19 pandemic, and the impact of changes on student learning behaviour at SMA Kristen Kapan. The research subjects were students, teachers, and the headmaster. The data were collected through observation, interviews, and documentation. The data were analysed through data reduction, data display, and drawing conclusions. The study shows that there are changes in students' learning behaviour, namely: the students were less active to ask questions, the students were less enthusiastic about learning, and the students were not active (silent) in joining the learning process. Besides, the impact is that the students begin to forget the school culture, students were more interested in playing online games and social media, lack discipline in learning, the students feel bored, and lack motivation.